2015
DOI: 10.1111/neup.12276
|View full text |Cite
|
Sign up to set email alerts
|

Primary central nervous system lymphomas and related diseases: Pathological characteristics and discussion of the differential diagnosis

Abstract: Although primary diffuse large B-cell lymphomas of the CNS are designated as primary CNS lymphomas according to the WHO Classification of Tumours of Haematopoietic and Lymphoid Tissue in 2008, a variety of other lymphomas (Burkitt lymphomas, EBV-positive diffuse large B-cell lymphoma of the elderly) and related diseases (lymphomatoid granulomatosis) that are also found in the CNS have been spotlighted in recent years. The histopathology of primary CNS Burkitt lymphomas mimics that of primary diffuse large B-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 40 publications
(139 reference statements)
1
35
0
1
Order By: Relevance
“…In this case, steroids and anti‐herpes virus agents did not appear to have any significant effects on EBV infection. Previous studies suggested the use of high‐dose antiviral therapy with azidothymidine and ganciclovir in patients with EBV‐positive primary CNS lymphomas . In addition, anti‐herpes viral therapy with acyclovir or foscarnet sodium may be proposed and corticosteroid therapy also appears to be reasonable when vasculitis is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, steroids and anti‐herpes virus agents did not appear to have any significant effects on EBV infection. Previous studies suggested the use of high‐dose antiviral therapy with azidothymidine and ganciclovir in patients with EBV‐positive primary CNS lymphomas . In addition, anti‐herpes viral therapy with acyclovir or foscarnet sodium may be proposed and corticosteroid therapy also appears to be reasonable when vasculitis is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a recent review of reported cases, EBV‐positive DLBCLs of the elderly have been shown to occur in the CNS of immunocompetent patients, arising in elderly patients aged >50 years without predisposing immunodeficiencies . A large cohort study of the prevalence and clinicopathological features of EBV‐positive primary CNS DLBCLs of the elderly, reported that 4% to 13.6% of cases expressing EBV sequences by in situ hybridization occur in immunocompetent patients . Therefore, it is important to consider the role of EBV in the pathogenesis of PCNSLs.…”
Section: Introductionmentioning
confidence: 99%
“…Primary CNS B-cell lymphoma, also a rare variant of DLBCL, has a proclivity to show angiocentric proliferation of neoplastic B cells [26]. In one instance, the perivascular growth pattern in the CNS in a patient with established IVLBCL resulted in an entirely separate diagnosis of primary CNS lymphoma being made, potentially creating unnecessary confusion [6].…”
Section: Discussionmentioning
confidence: 99%